2008
DOI: 10.1155/2008/849156
|View full text |Cite
|
Sign up to set email alerts
|

Frequent EGFR Positivity and Overexpression in High-Grade Areas of Human MPNSTs

Abstract: Malignant peripheral nerve sheath tumours (MPNSTs) are highly malignant and resistant. Transformation might implicate up regulation of epidermal growth factor receptor (EGFR). Fifty-two MPNST samples were studied for EGFR, Ki-67, p53, and survivin expression by immunohistochemistry and for EGFR amplification by in situ hybridization. Results were correlated with clinical data. EGFR RNA was also quantified by RT-PCR in 20 other MPNSTs and 14 dermal neurofibromas. Half of the patients had a neurofibromatosis typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 30 publications
(37 reference statements)
1
28
1
Order By: Relevance
“…These findings suggest that, whereas neurofibromin loss might contribute to AKT/mTOR deregulation, other molecular derangements acquired throughout the tumorigenic process may also be relevant. For example, among other potential mechanisms, overexpression and activation of the EGFR and c-Met tyrosine kinase receptors as well as loss of PTEN expression have been identified in MPNST (25)(26)(27)(28)(33)(34)(35)(36). No difference in AKT/mTOR activation could be identified when we compared NF1-associated and sporadic MPNST samples.…”
Section: Discussionmentioning
confidence: 87%
“…These findings suggest that, whereas neurofibromin loss might contribute to AKT/mTOR deregulation, other molecular derangements acquired throughout the tumorigenic process may also be relevant. For example, among other potential mechanisms, overexpression and activation of the EGFR and c-Met tyrosine kinase receptors as well as loss of PTEN expression have been identified in MPNST (25)(26)(27)(28)(33)(34)(35)(36). No difference in AKT/mTOR activation could be identified when we compared NF1-associated and sporadic MPNST samples.…”
Section: Discussionmentioning
confidence: 87%
“…Overexpression of survivin mRNA in MPNST compared to neurofibroma has been observed by three independent groups (16, 18, 19). Finally, a recent immunohistochemistry-based study demonstrated survivin protein expression in 52 human MPNST samples (20). Building on these initial observations, the current study sought to further determine the potential role of survivin as a MPNST biomarker, to elucidate the functional consequences of survivin over-expression in these tumors, and, most importantly, to assess the efficacy of survivin blockade as an anti-MPNST therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have implicated EGFR as a key oncogenic target in MPNST that is overexpressed in more than two-thirds of patients and associated with high-grade, p53 positivity and invasiveness [21,29,[34][35][36][37][38]. Despite a sound rationale and the fact that MPNST derived from patients and NF1 +/-…”
Section: Investigational Drugs In Clinical Trialsmentioning
confidence: 99%
“…+/-mice can be stimulated by epidermal growth factor and inhibited by EGFR inhibitors [36][37][38], a phase II trial with EGFR inhibitor erlotinib, the first targeted agent used in a NF1-associated MPNST, largely failed [39]. Other inhibitors have targeted PDGFR, which also shows an increased expression of both proteins in MPNSTs and carries prognostic relevance [29,40,41].…”
Section: /Tp53mentioning
confidence: 99%